TGR5 Agonist INT-777 Alleviates Inflammatory Neurodegeneration in Parkinson's Disease Mouse Model by Modulating Mitochondrial Dynamics in Microglia. (10th May 2022) - Huang, Rui; Gao, Yuyuan; Chen, Jianing; Duan, Qingrui; He, Peikun; Zhang, Jiahui; Huang, Heling; Zhang, Qingxi; Ma, Guixian; Zhang, Yuhu; Nie, Kun; Wang, Lijuan
Graphical abstract: Highlights: INT-777 alleviated motor deficits and cognitive impairment in a MPTP-induced PD model. INT-777 inhibited neuronal death and microglia activation in three brain regions. INT-777 suppressed microglia activation in the hippocampus via TNF signaling. INT-777 reversed microglial mitochondrial damage through TGR5 to inhibit TNF-α levels. INT-777 prevented neurodegeneration by inhibiting the release of TNF-α from microglia. Abstract: Parkinson's disease (PD) is one of the most common chronic progressive neurodegenerative diseases that affects both motor and non-motor functions. Bile acids modulate the immune system by targeting brain receptors. INT-777, a 6α-ethyl-23(S)-methyl derivative of cholic acid (S-EMCA), acts as an agonist for Takeda G protein-coupled receptor-5 (TGR5) and has neuroprotective properties. However, the effects of INT-777 on PD have not yet been investigated. In a subchronic PD model, mice treated with 1-Methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) developed motor deficits and cognitive impairment that were ameliorated after intranasal administration of INT-777. INT-777 prevented MPTP-induced neurodegeneration and microglia activation in the substantia nigra pars compacta, hippocampus, and cortical layer V. Based on bioinformatics and wet lab data, INT-777 inhibited microglia activation by suppressing the release of tumor necrosis factor alpha (TNF-α) in the hippocampus, along with secondary chemokines (C–C motif ligand 3 (CCL3) and CCL6) in these three brain regions. INT-777 inhibited TNF-α production by repairing mitochondrial damage, which was associated with nuclear factor-erythroid 2-related factor-2 (NRF2) activation and p62/LC3B-mediated autophagy. INT-777 reversed the downregulation of heme oxygenase-1 (HO1), NAD(P)H quinone oxidoreductase-1 (NQO1) and accumulation of p62 in microglia treated with 1-methyl-4-phenylpyridinium (MPP+). However, TGR5 knockdown in microglia abolished INT-777′s inhibition of TNF-α release, resulting in neuronal death. Therefore, PD cognitive impairment is associated with hippocampal TNF-α elevation as a result of mitochondrial damage in microglia. Our data reveal the potential role of TGR5 in modulating inflammation-mediated neurodegeneration in PD, and provides new insights for bile acid metabolites as promising disease-modifying drugs for PD.